2011
DOI: 10.1021/ef200302d
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Water-Extractable Carboxylic Acids in Crude Oil on Wettability in Carbonates

Abstract: The acidic components of the crude oil have a profound effect on the initial wetting conditions and possible wettability alteration by seawater in carbonates. In this work, three types of crude oils with different concentrations of waterextractable acidic components were prepared from a base oil: (1) a reference oil, RES-40 [acid number (AN) = 1.90 mg of KOH/g and base number (BN) = 0.51 mg of KOH/g], (2) a treated oil depleted in water-extractable acidic components, termed treated oil (TO) (AN = 1.50 mg of KO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(39 citation statements)
references
References 22 publications
3
36
0
Order By: Relevance
“…Standnes and Austad [91] also claim that carboxyl groups are the most active polar functional groups of crude oil in adsorbing organic material onto the chalk surface. Several other authors [152,[160][161][162][163] have shown that long chain acids are the most effective among researched acidic species to alter the carbonate rock to a…”
Section: Carbonate Rocksmentioning
confidence: 99%
“…Standnes and Austad [91] also claim that carboxyl groups are the most active polar functional groups of crude oil in adsorbing organic material onto the chalk surface. Several other authors [152,[160][161][162][163] have shown that long chain acids are the most effective among researched acidic species to alter the carbonate rock to a…”
Section: Carbonate Rocksmentioning
confidence: 99%
“…Standnes and Austad [93] also claim that carboxyl groups are the most active polar functional groups of the crude oil in adsorbing organic material onto the chalk surface. Several other authors [88,[98][99][100][101] have shown that long chain acids are the most effective among researched acidic species to alter the carbonate rock to a more oil-wet state. Despite that the effect of basic materials on wettability was not widely studied, Puntervold, et al [64], observed that an increase in the amount of natural bases led to decrease in waterwetness as AN was held constant.…”
Section: Crude Oil Compositionmentioning
confidence: 99%
“…Several laboratory studies have shown a positive LSE in carbonates [1,[19][20][21] however, there are only a few cases demonstrating a negligible LSE [22,23] . Traditionally, the LSE has been investigated through coreflooding and spontaneous imbibition experiments illustrating further oil recovery [19][20][21][24][25][26][27][28][29][30][31][32][33][34]. In addition, the LSE has been studied through other experimental means such as contact angle measurement [35], nuclear magnetic response [36] and a very limited amount of experimental work on zeta potential/surface charges [37][38][39].…”
Section: Introductionmentioning
confidence: 99%